SOCIAL WORK AND HUMAN RIGHTS: A SOCIOLOGICAL APPROACH TO ADVOCACY AND CHANGE - Muhammad Arslan; Maryam Shaukat (International Journal of Contemporary Issues in Social Sciences, 2024)
This article explores the intersection of social work and human rights from a sociological perspective, emphasizing the critical role social workers play in advocating for marginalized communities and promoting social change. By examining the historical evolution of social work and its integration with human rights principles, the article highlights how social work has developed as a profession committed to social justice and the protection of human dignity. Theoretical frameworks such as structural functionalism, conflict theory, and symbolic interactionism are utilized to analyze the social structures and power dynamics that contribute to social inequalities. The article also discusses various advocacy strategies employed by social workers, including community organizing, policy advocacy, and direct support, and presents case studies of successful initiatives that have led to significant human rights advancements. Furthermore, the challenges and barriers faced by social workers in their advocacy efforts are explored, along with the essential skills and competencies required for effective practice. The article concludes with a discussion of emerging trends and future directions in social work and human rights, emphasizing the ongoing need for social workers to champion human rights and contribute to the development of just and equitable societies.